Desarrollo de habilidades cognitivas del aprendizaje significativo. - Toscano Gómez, Alex Javier (2019)
The purpose of this research project was to improve meaningful learning through the adequate development of cognitive skills based on the theoretical-methodological conceptions demanded by the teaching-learning process, it is important to point out the role of the development of skills for Integrated formation of the child, especially in classrooms of the fourth year of basic education of the educational unit "" Our Lady of Pompeii "of the city of Saquisilí where an elite education is sought. So that the work was based on the basic conceptions of the modern constructivist approach, for which it will be based on the main authors such as: Ausubel, Vigotsky, and Piaget. The project was presented as innovative, in order to motivate the teacher to use the characteristics that the child presents to learn and develop their learning in a meaningful and appropriate way. A field study was carried out combining different methods such as: observation, surveys, among others, to identify which strategies to apply during the development of their classes. The results obtained by means of the fieldwork applying techniques, will allow to give a judgment of value on the problem of study and will admit later to recommend actions to overcome the institutional failures; In this way the project will generate a practical pedagogical and curricular contribution that will have a positive impact on the socio-educational scope of the educational community.